2021
DOI: 10.1021/acsami.1c05722
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Synthesis of Pd Nanocatalysts on Defect-Engineered CeO2 for CO2 Hydrogenation

Abstract: The size effects of metal catalysts have been widely investigated to optimize their catalytic activity and selectivity. However, the size-controllable synthesis of uniform supported metal nanoparticles without surfactants and/or additives remains a great challenge. Herein, we developed a green, surfactant-free, and universal strategy to tailor the sizes of uniform Pd nanoparticles on metal oxides by an electroless chemical deposition method via defect engineering of supports. The nucleation and growth mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…Jiang et al reported that the catalytic activity of CO 2 methanation over the Rh/TiO 2 catalyst is 2 and 14 times higher than those over Rh/Al 2 O 3 and Rh/ZnO catalysts, respectively, which is mainly attributed to the unique electronic structures of Rh and TiO 2 that are associated with stronger interaction of Rh–TiO 2 interfaces . It has been frequently reported that ceria (CeO 2 ), in view of their ready redox property and high surface oxygen vacancy concentrations to activate CO 2 , have been widely used as the catalyst support to load metals for CO 2 hydrogenation , among which CeO 2 -supported Rh (Rh/CeO 2 ) catalysts are highly active and exhibit potential applications. , Marin et al compared the catalytic performance of various metal oxide and aluminosilicate (SiO 2 , Al 2 O 3 , CeO 2 , ZSM-5, and MCM-41)-supported metal (Pd, Rh, and Ni) catalysts for CO 2 methanation and demonstrated Rh/CeO 2 as the most active catalyst for CO 2 conversion . However, there is still a lack of systematical studies for Rh–CeO 2 interfacial catalysis in CO 2 hydrogenation, which limits the fundamental understanding of the catalytic active sites and consequently the development of more efficient Rh/CeO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al reported that the catalytic activity of CO 2 methanation over the Rh/TiO 2 catalyst is 2 and 14 times higher than those over Rh/Al 2 O 3 and Rh/ZnO catalysts, respectively, which is mainly attributed to the unique electronic structures of Rh and TiO 2 that are associated with stronger interaction of Rh–TiO 2 interfaces . It has been frequently reported that ceria (CeO 2 ), in view of their ready redox property and high surface oxygen vacancy concentrations to activate CO 2 , have been widely used as the catalyst support to load metals for CO 2 hydrogenation , among which CeO 2 -supported Rh (Rh/CeO 2 ) catalysts are highly active and exhibit potential applications. , Marin et al compared the catalytic performance of various metal oxide and aluminosilicate (SiO 2 , Al 2 O 3 , CeO 2 , ZSM-5, and MCM-41)-supported metal (Pd, Rh, and Ni) catalysts for CO 2 methanation and demonstrated Rh/CeO 2 as the most active catalyst for CO 2 conversion . However, there is still a lack of systematical studies for Rh–CeO 2 interfacial catalysis in CO 2 hydrogenation, which limits the fundamental understanding of the catalytic active sites and consequently the development of more efficient Rh/CeO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the different conversion alternatives, CO 2 hydrogenation under the condition of atmospheric pressure has two main products, i.e., CO and CH 4 generated via the reverse water–gas shift (RWGS) and Sabatier reactions, respectively. , Previous studies indicated that oxide-supported metal catalysts exhibit great potential in this reaction and the catalytic performance is sensitive to the structures of the metal–oxide interfaces that are determined by the natures of both the support and supported metal. Compared to other supported metals, oxide-supported Ni catalysts possess prominent advantages due to their high catalytic properties but much lower costs. Previously, different oxides, including CeO 2 , TiO 2 , ZrO 2 , and Y 2 O 3 , have been used as the support to investigate the catalysis of oxide-supported Ni catalysts in CO 2 hydrogenation, among which Ni/CeO 2 catalysts are highly active that is beneficial from the unique surface characteristic of ceria. …”
Section: Introductionmentioning
confidence: 99%
“…In China, synthetic natural gas (SNG) production from coal has been of great importance due to the abundant coal reserves, while there is a shortage of natural gas . In SNG production, methane synthesis from CO and H 2 is the key step. , However, in the process of coal to gas process, some sulfur-containing gases are also formed, which results in rapid poisoning and deactivation of most catalysts. To address this problem, two-dimensional MoS 2 has attracted much attention due to its good sulfur resistance and hydrogenation catalytic activity, , which can shorten the coal-to-syngas process without the need for desulfurization, while the research and development of catalysts for high-activity sulfur-resistant methanation has been a challenging task in short-process coal-to-syngas production.…”
Section: Introductionmentioning
confidence: 99%